Student wellbeing, resilience and moral identity: Does the school climate have an impact? - Riekie, Helen Mary (Curtin University, 2016)
The overarching aim of this study was to examine the impact of school climate on students’ wellbeing, resilience and moral identity. Two questionnaires, one to assess school climate and another to assess the three outcomes, were administered to a sample of 618 students from 15 South Australian independent schools. The hypothesised relationships were investigated using structural equation modelling. The results could guide schools in building environments that engender positive, resilient citizens with strong moral identities.